2017
DOI: 10.5543/tkda.2017.03256
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myocardial Infarction Shortly After Valve-in Valve Transcatheter Aortic Valve Implantation (TAVI) Successfully Managed With An Apparently Challenging Percutaneous Coronary Intervention

Abstract: In recent years, transcatheter aortic valve implantation (TAVI) has been considered a novel option for the management of surgically high-risk patients requiring aortic valve replacement. Presently described is a case of acute coronary syndrome (ACS) managed with a challenging primary percutaneous coronary intervention (PCI) shortly after a valve-in-valve TAVI intervention. This case highlights 2 important issues: PCI may be an option for the management of coronary heart disease in patients after TAVI even in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Interestingly, clinicians are generally inclined to consider these life-threatening readmissions as part of a natural and anticipated course of these high-risk patients, and do not contemplate over any spesific triggers and mechanisms underlying these coronary ischemic syndromes emerging after TAVI. In our clinical practice, we also encounter such cases readmitted with acute coronary ischemic syndromes emerging without a spesific trigger after TAVI 10 . Similarly, readmissions with acute myocardial infarction (AMI) following TAVI were also reported in previous large-scale studies 8 , 9 .…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…Interestingly, clinicians are generally inclined to consider these life-threatening readmissions as part of a natural and anticipated course of these high-risk patients, and do not contemplate over any spesific triggers and mechanisms underlying these coronary ischemic syndromes emerging after TAVI. In our clinical practice, we also encounter such cases readmitted with acute coronary ischemic syndromes emerging without a spesific trigger after TAVI 10 . Similarly, readmissions with acute myocardial infarction (AMI) following TAVI were also reported in previous large-scale studies 8 , 9 .…”
Section: Introductionmentioning
confidence: 68%
“…Importantly, this was reportedly the first study directly comparing surgical and transcatheter aortic valve interventions in patients with a relatively low surgical risk 4 . Taken together, the incidence of AMI might be relatively rare in the short and mid terms after TAVI, and appears to be comparable between self and baloon expandable valves 8, 9, 10, 11. However, there exists an upward temporal trend in the incidence of AMI readmissions on longer clinical follow-up 12, 13…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In the recent years, transcatheter aortic valve implantation (TAVI) has gained a significant reputation as an alternative option for the management of aortic valve disease particularly in the setting of high-risk conditions for surgical aortic valve replacement (SAVR) (1)(2)(3). In the wellknown PARTNER-1 trial, TAVI was found to be associated with a significant mortality benefit in comparison to standard treatment among patients with aortic valve stenosis (AVS) (1).…”
mentioning
confidence: 99%